Asbestos: use, bans and disease burden in Europe - Kameda, Takashi; Takahashi, Ken; Kim, Rokho; Jiang, Ying; Movahed, Mehrnoosh; Park, Eun-Kee; Rantanen, Jorma (Bulletin of the World Health Organization, 2014)
To analyse national data on asbestos use and related diseases in the European Region of the World Health Organization (WHO). For each of the 53 countries, per capita asbestos use (kg/capita/year) and age-adjusted mortality rates (deaths/million persons/year) due to mesothelioma and asbestosis were calculated using the databases of the United States Geological Survey and WHO, respectively. Countries were further categorized by ban status: early-ban (ban adopted by 2000, n = 17), late-ban (ban adopted 2001-2013, n = 17), and no-ban (n = 19). Between 1920-2012, the highest per capita asbestos use was found in the no-ban group. After 2000, early-ban and late-ban groups reduced their asbestos use levels to less than or equal to 0.1 kg/capita/year, respectively, while the no-ban group maintained a very high use at 2.2 kg/capita/year. Between 1994 and 2010, the European Region registered 106,180 deaths from mesothelioma and asbestosis, accounting for 60% of such deaths worldwide. In the early-ban and late-ban groups, 16/17 and 15/17 countries, respectively, reported mesothelioma data to WHO, while only 6/19 countries in the no-ban group reported such data. The age-adjusted mortality rates for mesothelioma for the early-ban, late-ban and no-ban groups were 9.4, 3.7 and 3.2 deaths/million persons/year, respectively. Asbestosis rates for the groups were 0.8, 0.9 and 1.5 deaths/million persons/year, respectively. Within the European Region, the early-ban countries reported most of the current asbestos-related deaths. However, this might shift to the no-ban countries, since the disease burden will likely increase in these countries due the heavy use of asbestos.